Homogeneously Large Polarons in Aromatic Passivators Improves Charge Transport between Perovskite Grains for >24 % Efficiency in Photovoltaics. Issue 14 (15th February 2022) - Zhao, Jia‐Hui; Mu, Xijiao; Wang, Luyao; Fang, Zihan; Zou, Xiaoxin; Cao, Jing
Abstract: Aromatic passivators, such as porphyrin, with large π‐backbones have attracted considerable attention to boost the charge carrier in polycrystalline perovskite films, thus enabling the fabrication of efficient and stable perovskite solar cells (PSCs). However, they often self‐assemble into supramolecules that probably influence the charge‐transfer process in the perovskite grain boundary. Here, by doping a monoamine Cu porphyrin into perovskite films, two porphyrin‐based self‐assembled supramolecules were successfully prepared between perovskite grains. Crystal structures and theoretical analyses reveal the presence of a stronger interaction between the amine units and the central Cu ions of neighbouring porphyrins in one of the supramolecules. This has a modified effect on the dipole direction of the porphyrins to be quantized as homogeneously large polarons (HLPs) in a periodic lattice. The porphyrin supramolecules can stabilize perovskite grain boundaries to greatly improve the stability of PSCs, while the HLPs‐featured supramolecule facilitates hole transport across perovskite grains to remarkably increase the cell performance to as high as 24.2 %. This work proves that the modulation of the intermolecular interaction of aromatic passivators to yield HLPs is crucial for the cascaded acceleration of charge transport between perovskite grains. Abstract : Charge transport behavior of two amine Cu porphyrin supramolecules with different stacking interactions in perovskite grain boundaries was investigated in detail. Results prove that the construction of homogeneously large polarons (HLPs) in aromatic passivators is a key factor for the charge transport between perovskite grains. This work also affords a new strategy to design new optoelectronic materials with improved charge mobilities.